Analysis of Hardness Level in Enim River for Demineralization Water Process in Thermal Power Plant Tanjung Enim - Asri Alfiah Fajri; Tb. Ade Rahmatullah; Gurruh Dwi Septano; Nasaruddin (Jurnal Informasi dan Teknologi, 2025)
Demineralization water is removal of dissolved ionic mineral impurities present in water and other liquids. Mineral content in water can cause crusts in power plant equipment such as boilers and turbine, lowering yield and selectivity values in the reaction process. The aim of the research is to diagnose the conditions of water process Tanjung Enim thermal power plant with standard value of ASME CRTD Vol. 34 and Power Plant water treatment standard. Demineralization Water treatment process starts from Multimedia Filter (MMF), Carbon Filter (CF), Reverse Osmosis (RO), Electrodeionization. Demineralization water sampling taken in January, february, march and April. The water sampling used in RAW Water, Feed RO, Electrodeionization process, feed water and boiler drum to measure the parameters of pH, conductivity, turbidity, Fe, Cl2 and Si02, P04 and ions of Na+, Fe+, Cu+ some of parameters result the fluctuative value but still in both of water treatment standard.